Voter Perceptions of Political Accountability in the 2025 Philippine Senate Elections - Jesus, Dennis A. De; Benter, Jocelyn B.; Austria, Windel C. (NPRC Journal of Multidisciplinary Research, 2026)
Purpose: This study examines how Filipino voters evaluate political accountability dimensions—specifically answerability, enforceability, and responsiveness—following the 2025 Philippine Senate elections. It identifies which accountability dimensions and policy issues voters prioritize, explores demographic differences in accountability perceptions, and analyzes how those perceptions influence voting preferences.Methods: A cross-sectional quantitative design was employed using a post-election survey of 600 registered Filipino voters. Stratified sampling was applied based on geographic location (Luzon, Visayas, Mindanao), age, gender, and educational attainment. Data were collected from May to June 2025 using a validated 15-item questionnaire (Cronbach’s α = 0.89). Statistical analyses included frequency distributions, mean scores, one-way ANOVA, and Chi-square tests, with a 95% confidence level and ±4% margin of error.Results: Voters rated anti-corruption stance (mean = 4.74), candidate integrity (4.69), and transparency (4.57) as the most valued accountability dimensions, while responsiveness received the lowest rating (4.10). The top policy priority was anti-corruption measures (68.5%), followed by job creation (59.2%) and poverty reduction (54.1%). Demographic analysis showed strong participation by voters aged 18–40, with higher educational attainment associated with more critical candidate evaluation. No significant gender-based differences were found.Conclusion: Filipino voters prioritize ethical, integrity-based dimensions of political accountability over service delivery responsiveness. However, there is persistent skepticism about the effectiveness of electoral and institutional mechanisms in enforcing post-election accountability, indicating an “accountability paradox” where accountability remains candidate-centered rather than institution-driven.